Impact of Time-Varying Intensity of Mechanical Ventilation on 28-Day Mortality Depends on Fluid Balance in Patients With Acute Respiratory Distress Syndrome: A Retrospective Cohort Study - Hu, Weiwei; Zhang, Suming; He, Zhengyu; Zhou, Yang; Wang, Ziwen; Zhang, Yang; Zang, Baohe; Zhao, Wenjing; Chao, Yali (Frontiers in Medicine, 2022)
Background: Recent studies mainly focused on the association between baseline intensity of mechanical ventilation (driving pressure or mechanical power) and mortality of acute respiratory distress syndrome (ARDS). Whether the association between the time-varying intensity of mechanical ventilation and mortality are significant, and varies according to the fluid balance trajectories，remains uncertain. Methods: We conducted a secondary analysis based on the NHLBI ARDS Network’s Fluid and Catheter Treatment Trail (FACTT). The primary outcome was 28-day mortality. Group-based trajectory modeling was employed to identify phenotypes based on fluid balance trajectories. Bayesian joint models were used to account for informative censoring due to death during follow-up. Results: A total of 1000 patients with ARDS were included in the analysis. Our study identified two phenotypes of ARDS, and compared to patients with Early-Negative Fluid Balance (Early-NFB), Patients with Persistent-Positive Fluid Balance (Persistent-PFB) accompanied by higher tidal volume, higher static driving pressure, higher mechanical power and lower PaO2/FiO2, over time during mechanical ventilation. The 28-day mortality was 14.8% in Early-NFB and 49.6% in Persistent-PFB (p<0.001). In the Bayesian joint models, the hazard ratio of 28-day death for time-varying static driving pressure (HR 1.03 (95% CI 1.01-1.05; p<0.001)) and mechanical power (HR 1.01 (95% CI 1.002-1.02; p=0.01)) were significant in patients with Early-NFB, but not in patients with Persistent-PFB. Conclusion: Time-varying intensity of mechanical ventilation was associated with 28-day mortality of ARDS in patient with Early-NFB, but not in patients with Persistent-PFB.